The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1007/s005350300063
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of diabetes mellitus in Japanese patients infected chronically with hepatitis C virus

Abstract: Taken together, the findings indicate that cirrhosis appears to be a more important predictor of glucose intolerance than HCV infection, and the combination of both factors increases the risk of DM in our populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
79
2
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(89 citation statements)
references
References 20 publications
6
79
2
2
Order By: Relevance
“…11 Inconsistent results have also been reported about the association between hepatitis C infection and type 2 diabetes. [12][13][14][15][16][17][18][19] These inconsistencies may be due to small sample sizes and selected patients from hospital, so a large population-based study is again desirable.…”
Section: Introductionmentioning
confidence: 99%
“…11 Inconsistent results have also been reported about the association between hepatitis C infection and type 2 diabetes. [12][13][14][15][16][17][18][19] These inconsistencies may be due to small sample sizes and selected patients from hospital, so a large population-based study is again desirable.…”
Section: Introductionmentioning
confidence: 99%
“…Various chronic liver diseases are associated with DM (8,9). Many studies report that HCV increases the incidence of DM (13)(14)(15)(16)(17). The hepatitis C virus induces DM through insulin resistance via a variety of direct and indirect mechanisms (12).…”
Section: Discussionmentioning
confidence: 99%
“…An estimated 1.4-46.7% of patients infected with HCV also have DM, and a meta-analysis shows HCV infection increases the risk of developing DM by approximately 1.7-fold compared to that in non-infected controls (16). Diabetes mellitus also occasionally occurs in HBV-infected patients; previous studies indicate the prevalence rate of DM is 6.3-12% in HBV infection (13)(14)(15)18). However, a recent population-based cohort study suggested that HBV infection had no effect on DM development (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ZG16p is associated with lipid microdomains ('rafts') and affects the protein synthesis and intracellular transport of secretory proteins and maturation of zymogens in ZGs [31][32][33][34] . HCV infection and chronic hepatopathy caused by HCV are significantly associated with diabetes, and reduction of glucose tolerance is related to the severity of chronic hepatitis C [35,36] . The result of our experiment showed that interaction occurred between HCV F and ZG16p, thus providing a new clue for revealing the function of HCV F protein and relationship between pathogenesis of HCV and diabetes mellitus.…”
Section: Analysis Of Cdna Sequence and Homologymentioning
confidence: 99%